CORPORATE LIABILITY FORMULATION POLICY ACCORDING TO ARTICLE 101 OF LAW NUMBER 31 OF 2004 JUNCTO LAW NUMBER 45 OF 2009 CONCERNING FISHERIES IN TERM OF CRIMINAL LEGAL REFORM IN INDONESIA - Vivi Tri Kasih; Antory Royan Adyan; Herlambang Herlambang (Universitas Bengkulu, 2021)
The corporation is the brain and source of funds for all illegal fishing activities and other crimes that occur along the chain of fishing business activities. According to Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Fisheries, Article 101 states that: